The Change of Function of Rejung Arts in Pagaralam City - Sari, Reza Nepilia; Utomo, Udi (Universitas Negeri Semarang, 2018)
The arts of Rejung is a poem delivered through singing or song, accompanied by a single guitar (one guitar), has a rhythm and ornamental tones delivered in accordance with the theme and vocal character of the performer or Rejung artist. Rejung arts is a form of expression of a cultural society in Pagaralam which has a variety of functions according to the interests and circumstances of society. The purpose of the study was to analyze the socio-cultural changes and its effect on the function of Rejung arts in Pagaralam. The science used here is sociology, it is to describe social changes in a society that affects the function of Rejung arts in Pagaralam. The research method is descriptive qualitative. The technique of data collection in this research are observation, interview, and documentation. The technique of data validity to examine credibility of data is through triangulation. Triangulation of source was done for the process of examination by checking data from several sources. The technique of data analysis used analysis procedur of Miles’ and Huberman’s interactive, i.e., data reduction from the object of Rejung arts. The data is in the form of written document, visual and audio which have been identified, verified, arranged, grouped, and classified in accordance with the research focus. The change of function of Rejung arts because of the less interest from societies, especially the young generation to display and to appreciate Rejung arts as a form of traditional arts. It causes the losing of a tradition and values of inherited arts from generation to generation.